Encoding of Touch Intensity But Not Pleasantness in Human Primary Somatosensory Cortex - Case, Laura K. (J Neurosci, 2016)
Growing interest in affective touch has delineated a neural network that bypasses primary somatosensory cortex (S1). Several recent studies, however, have cast doubt on the segregation of touch discrimination and affect, suggesting that S1 also encodes affective qualities. We used functional magnetic resonance imaging (fMRI) and repetitive transcranial magnetic stimulation (rTMS) to examine the role of S1 in processing touch intensity and pleasantness. Twenty-six healthy human adults rated brushing on the hand during fMRI. Intensity ratings significantly predicted activation in S1, whereas pleasantness ratings predicted activation only in the anterior cingulate cortex. Nineteen subjects also received inhibitory rTMS over right hemisphere S1 and the vertex (control). After S1 rTMS, but not after vertex rTMS, sensory discrimination was reduced and subjects with reduced sensory discrimination rated touch as more intense. In contrast, rTMS did not alter ratings of touch pleasantness. Our findings support divergent neural processing of touch intensity and pleasantness, with affective touch encoded outside of S1. SIGNIFICANCE STATEMENT Growing interest in affective touch has identified a neural network that bypasses primary somatosensory cortex (S1). Several recent studies, however, cast doubt on the separation of touch discrimination and affect. We used functional magnetic resonance imaging and repetitive transcranial magnetic stimulation to demonstrate the representation of touch discrimination and intensity in S1, but the representation of pleasantness in the anterior cingulate cortex, not S1. Our findings support divergent neural processing of touch intensity and pleasantness, with affective touch encoded outside of S1. Our study contributes to growing delineation of the affective touch system, a crucial step in understanding its dysregulation in numerous clinical conditions such as autism, eating disorders, depression, and chronic pain.